Metode Zero Suffix Dalam Meminimumkan Biaya Pengiriman Barang (Studi Kasus PT. Aspac Cargo) - Ega Rizka Wahyuni; Arnellis Arnellis (Journal of Mathematics UNP, 2021)
Logistics   business   activities, expedition   services   and   couriers   are   sectors   that experienced  a  growth  spurt  and  even  showed  an  increase  in  transaction  value.  PT.  Asia  Pacific Dirgantara  (Aspac  Cargo)  is  an  expedition  service  company  that  requires  a  mechanism  in  the distribution  of  goods.  In  the  distribution  of  goods,  planning  to  determine  shipping  costs  is  very influential. Good planning makes PT. Aspac Cargo is superior to other shipping companies so that it can get maximum profit. The purpose of this study was to determine the minimum cost of shipping goods at PT. Aspac Cargo using the Zero Suffix method and the minimum cost percentage obtained by PT. Aspac Cargo in minimizing the cost of shipping goods using the Zero Suffix method. This research is applied research and the data used are data on delivery of goods, data on demand for delivery  of  goods  and  data  on  the  cost  of  shipping  goods  from  the  city  of  origin  to  the  city  of destination. The final result of the application of the Zero Suffix method to minimize the cost of shipping goods at PT. Aspac Cargo is Rp. 322,322,000 and the  percentage  of the  minimum cost obtained  by  PT.  Aspac  Cargo  in  minimizing  the  cost  of  shipping  goods  using  the  Zero  Suffix method, which is 16.9%